2022
DOI: 10.3389/fphys.2022.1004192
|View full text |Cite
|
Sign up to set email alerts
|

Antennae-abundant expression of candidate cytochrome P450 genes associated with odorant degradation in the asian citrus psyllid, Diaphorina citri

Abstract: The Asian citrus psyllid, Diaphorina citri, is a notorious pest that is an efficient vector for Candidatus Liberibacter asiaticus (CLas), the causal agent of citrus huanglongbing (HLB). The olfactory system of insects is crucial for foraging and mating behavior. Antennae-abundant odorant degrading enzymes (ODEs), including cytochrome P450 (CYPs), are important in degrading redundant odorant molecules to recover the insect olfactory. In this study, to isolate the antennal CYP genes of D. citri, we generated fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In this study, a total of seven antennae enriched LeCYP genes were identified. Our number of antennal CYP genes in L. erysimi is comparable to those found in other insect species, such as seven antennae-abundant CYPs were documented in D. citri (Kuang et al, 2022), as well as four CYPs (CYP4L4, CYP4S4, CYP9A13, and CYP4G20) of Mamestra brassicae and four CYPs (CYP6DE1, CYP6DJ1, CYP6BW1, and CYP6BW3) of D. ponderosae have been found to be highly expressed in the antennae (Maïbèche-Coisne et al, 2002;Maïbèche-Coisne et al, 2005;Chiu et al, 2019a;Chiu et al, 2019b;Chiu et al, 2019c). Insect P450 genes are commonly divided into four clades, which include CYP2, CYP3, CYP4, and the mitochondrial CYP.…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, a total of seven antennae enriched LeCYP genes were identified. Our number of antennal CYP genes in L. erysimi is comparable to those found in other insect species, such as seven antennae-abundant CYPs were documented in D. citri (Kuang et al, 2022), as well as four CYPs (CYP4L4, CYP4S4, CYP9A13, and CYP4G20) of Mamestra brassicae and four CYPs (CYP6DE1, CYP6DJ1, CYP6BW1, and CYP6BW3) of D. ponderosae have been found to be highly expressed in the antennae (Maïbèche-Coisne et al, 2002;Maïbèche-Coisne et al, 2005;Chiu et al, 2019a;Chiu et al, 2019b;Chiu et al, 2019c). Insect P450 genes are commonly divided into four clades, which include CYP2, CYP3, CYP4, and the mitochondrial CYP.…”
Section: Figuresupporting
confidence: 84%
“…The dataset submitted for phylogenetic analysis comprised the candidate CXE, CYP, GST, and UGT genes of L. erysimi in this study, their homologs from Acyrthosiphon pisum ( Ramsey et al, 2010 ), Aphis craccivora ( Yang et al, 2021 ), Aphis gossypii ( Pan et al, 2018 ), Myzus persicae ( Pan et al, 2019 ), Nilaparvata lugens ( Vontas et al, 2002 ; Zhou et al, 2013 ), Diaphorina citri ( Yu and Killiny, 2018 ; Tian et al, 2019 ; Wu et al, 2020 ; Kuang et al, 2022 ), Anopheles gambiae ( Ding et al, 2003 ), and Bombyx mori ( Yu et al, 2008 ); in addition to some well-identified ODE genes, including the studied antennal CXEs ( Ishida and Leal, 2005 ; 2008 ; Durand et al, 2010 ; Durand et al, 2011 ; He et al, 2015 ; Wei et al, 2021 ), CYPs ( Keeling et al, 2013 ; Chiu et al, 2019a ), GSTs ( Rogers et al, 1999 ; Li et al, 2018 ; Liu et al, 2021 ; Xia et al, 2022 ), and UGTs ( Wang et al, 1999 ; Bozzolan et al, 2014 ). The protein sequences were first aligned using CLUSTAL_X version 1.83.…”
Section: Methodsmentioning
confidence: 99%
“…The sequencing data was filtered to obtain clean reads with SOAPnuke (v1.5.2) by removing low‐quality reads (i.e., low‐quality base ratio >20%) and reads with adaptor sequences and/or unknown nucleotides (>5%). Transcriptome de novo assembly was conducted as previously described (Kuang et al, 2022). The unigenes were annotated using BLAST search against public databases including Nr, Nt, Swiss‐Prot, KEGG, KOG, Pfam, and GO, with a cut‐off E ‐value of 10 −5 .…”
Section: Methodsmentioning
confidence: 99%
“…The sequencing data was filtered to obtain clean reads with SOAPnuke (v1.5.2) by removing low-quality reads (i.e., low-quality base ratio >20%) and reads with adaptor sequences and/or unknown nucleotides (>5%). Transcriptome de novo assembly was conducted as previously described (Kuang et al, 2022).…”
Section: Illumina Sequencing and Data Processingmentioning
confidence: 99%